Glimepiride monotherapy in achieving good blood glucose control in type-2 diabetes mellitus: a prospective observational study (Medical Journal of Indonesia, 2009)
Aims Glimepiride is a sulphonylurea antihyperglycemic agent for oral therapy of type-2 diabetes mellitus. This study was carried out to evaluate glimepiride monotherapy in controlling blood glucose (HbA1c) in type-2 DM patients, its dosage, and safety profile. Methods This was a prospective observational study carried out at 4 private clinics in Semarang, Jambi, Mojokerto and Medan between October 2006 and September 2007 in outpatients of both gender, aged > 20 years, with type-2 DM, HbA1c > 7%, and received no oral antidiabetic treatment for at least 3 months. Glimepiride tablet was given once daily for 3 months. Results From 74 eligible patients, 18 patients were lost to follow-up and 56 patients completed this 3 months study, consisting of 26 treatment-naive patients and 30 previously treated patients. The initial and final doses of glimepiride were similar in both treatment-naive patients and previously treated patients (initial 2.0 mg, final 2.3 mg). The meanreduction of HbA1c levels was 1.8% (absolute) for all patients, higher in naive patients (2.3%) compared to previously treated patients (1.3%). Based on BMI, the mean reduction of HbA1c in 20 normal weight patients was 1.3%, and more marked in 20 obese patients (2.4%). The mean reduction of FBG levels in all patients was 54 mg/dL, more pronouncedin naive patients ( 83 mg/dL) compared to previously treated patients (30 mg/dL), but not affected by body weight. Bodyweight was increased during the study by a mean of 0.9 kg. No adverse event was encountered in any patient during 3 months monotherapy with glimepiride in the present study. Conclusion Glimepiride monotherapy in the present observational study in daily practice for 3 months was shown to be effective in reducing HbA1c and FBG levels, especially in treatment naive patients. Glimepiride in the present study was associated with weight gain, although not statistically signifi cant. No adverse event was reported in the present study. (Med J Indones 2009;18:170-8)